Fouling and wetting in membrane distillation (MD) and MD-bioreactor (MDBR) for wastewater reclamation - Goh, Shuwen (2013)
The membrane distillation (MD) process is seldom employed in wastewater reclamation since the high organic and nutrient in wastewater promote wetting. The MD bioreactor (MDBR) can remediate this by biologically removing retentate carbohydrates and proteins. However, the inclusion of biomass in the MDBR can result in biofouling and flux decline. The objectives of this work are to determine the effectiveness of the bioprocess in delaying membrane wetting (by removing organics and nutrients) and the significance of the biofouling on flux decline. From this work, the MDBR flux can be maintained at more than 6.8 L/m2 h (8% lower than the average MD flux) for at least 13 days. The faster flux decline in the MDBR is attributed to the thermal and mass transfer resistance of the biofilm but this can be controlled with periodic membrane cleaning and process optimization. Membrane fouling has been shown to compromise membrane hydrophobicity and accelerate wetting. By lowering the retentate organic and nutrient concentration, the MDBR has successfully delayed wetting by 1.7–3.6 times in this work, reducing the frequency of membrane cleaning and drying. With further process optimization, the MDBR could be a good option for reclamation of industrial wastewater with low volatile organic content and access to waste heat.